Uptake hydrogenase activity and ATP formation in Rhizobium leguminosarum bacteroids. - Nelson, L M (1982)
The role of uptake hydrogenase was studied in Rhizobium leguminosarum bacteroids from the nodules of Pisum sativum L. cv. Homesteader. Uptake hydrogenase activity, measured by the 3H2 uptake method, was dependent on O-consumption and was similar to H2 uptake measured by gas chromatography. Km for O2 of 0.0007 atm (0.0709 kPa) and a Km for H2 of 0.0074 atm (0.7498, kPa) were determined. H2 increased the rate of endogenous respiration by isolates with uptake hydrogenase (Hup+) but had no effect on an isolate lacking uptake hydrogenase (Hup-). A survey of 14 Hup+ isolates indicated a wide range of H2 uptake activities. Four of the isolates tested had activities similar to or higher than those found in two Hup+ Rhizobium japonicum strains. H2 uptake was strongly coupled to ATP formation in only 5 of the 14 isolates. H2 increased the optimal O2 level of C2H2 reduction by 0.01 atm and permitted enhanced C2H2 reduction at O2 levels above the optimum in both a coupled and an uncoupled isolate. At suboptimal O2 concentrations a small enhancement of C2H2 reduction by H2 was seen in two out of three isolates in which H2 oxidation was coupled to ATP formation. Thus, the main function of uptake hydrogenase in R. leguminosarum appears to be in the protection of nitrogenase from O2 damage.